Evaluating the Effect of Employee Stock Option Plans on the Financial Performance of Indian Construction & Infrastructure Companies - Sonali B. Ramchandani; Dr. Hemal B. Pandya (International Journal of Engineering and Management Research, 2019)
Competitive pressures to improve productivity continue to place significant demand upon organizations globally. To respond to these competitive pressures with the developed countries like USA, ESOPs (Employee Stock Ownership Plans) have also been adopted in developing country like India to increase the firm’s and employee’s performance and productivity by retaining the employees to a large extent. Employee Stock Ownership Plans are majorly utilized by many successful and competent companies across the world. The successes of the ESOP companies in countries like USA, Japan and UK etc. may largely be attributed to enhancement of firm’s performance and Employee productivity. These effects are becoming increasingly noticed across the world in recent years. Thus, this research is an empirical study carried out to evaluate the impact of ESOP on financial performance of ten listed Indian Construction and Infrastructural companies based on for a period of six years. The study analyzes three years pre and post period to the adoption of ESOPs for the selected companies and is based upon secondary data collected from company annual reports of the respective years. Company-wise Pre- and Post- ESOP adoption Analysis and Regression Analysis is carried out in the selected selector.